Academic stress and academic burnout in adolescents: a moderated mediating model - Gao, Xinhang (Frontiers in Psychology, 2023)
Objective This study aims to investigate the relationship and mechanisms of action among academic stress, academic anxiety, academic self-efficacy, and academic burnout among adolescents. Methods A study of 929 Chinese adolescents (53.71% males, mean age = 11.94 years, SD = 0.77) was conducted using the Study Stress Questionnaire, Academic Anxiety Subscale, Junior Middle School Students’ Learning Weariness Scale, and the Academic Self-efficacy Questionnaire. Results ①Academic stress was significantly and positively correlated with academic anxiety and academic burnout, and significantly and negatively correlated with academic self-efficacy. ②Academic anxiety partially mediated the relationship between academic stress and academic burnout. ③Academic self-efficacy significantly moderated the direct effect of academic stress on academic burnout, and higher academic self-efficacy could buffer the negative effect of academic stress. ④Academic self-efficacy significantly moderated the second half of the mediated model’s path (academic anxiety → academic burnout), that is, low academic self-efficacy amplified the risk effect of academic anxiety on academic burnout. Conclusion Academic anxiety partially mediates the relationship between academic stress and academic burnout, and this mediating role is moderated by academic self-efficacy.